Determinants of Online Purchase Decisions: The Roles of Trust, Price, and Product Quality among Graduate Students - Pahrul; Sahade; Sumiati Tahir; Nurhayani; Khaerun Nisa (Fundamental and Applied Management Journal, 2025)
This study examines the determinants of online purchase decisions among graduate students at Universitas Negeri Makassar, with particular attention to trust, price, and product quality. The study is significant because online transactions are characterized by uncertainty, limited physical inspection of products, and higher perceived risk, making these factors central to consumer decision-making. Conceptually, the study offers an integrated view of relational, economic, and product-related considerations in explaining online purchasing behavior. A descriptive quantitative approach was employed in this research. Data were collected through questionnaires administered to 100 graduate students who had previously purchased products online, selected using incidental non-probability sampling. The data were analyzed using multiple linear regression with the support of SPSS. The analysis focuses on both the partial and simultaneous effects of trust, price, and product quality on online purchase decisions. The study highlights that online purchasing decisions are closely associated with consumers’ confidence in sellers, price considerations, and evaluations of product quality. These findings imply that online businesses need to strengthen consumer trust, offer competitive pricing, and maintain product quality to encourage stronger purchase decisions. This study contributes to marketing management literature by emphasizing that online purchase decisions are shaped by both economic and relational factors.